Import competition and labor productivity - Bloch, Harry; McDonald, J. (Springer New York LLC, 2001)
The impact of import competition on labor productivity is examined using panel data for a sample of Australian manufacturing firms over the period 1984–1993. Import competition is found to interact with domestic competition; such the positive impact of import competition on the level and rate of growth of labor productivity rises with the degree of concentration among domestic producers. The results suggest that lowering border protection on manufactured imports into Australia has led to enhanced productivity from domestic producers, especially from those producers in highly concentrated industries.